Biomedical Optics 2008
DOI: 10.1364/biomed.2008.bmf2
|View full text |Cite
|
Sign up to set email alerts
|

Optical Design for Spatial-Spectral Volume Holographic Imaging System

Abstract: The spatial-spectral holographic imaging system ͑S 2-VHIS͒ is a promising alternative to confocal microscopy due to its capabilities to simultaneously image several sample depths with high resolution. However, the field of view of previously presented S 2-VHIS prototypes has been restricted to less than 200 m. We present experimental results of an improved S 2-VHIS design that has a field of view of ϳ1 mm while maintaining high resolution and dynamic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…The relay was configured for 1:1 imaging to image the pupil of the microscope objective at the hologram plane, which allows the hologram to be the limiting aperture of the system and reduces beam overfill issues. 18 The holograms used in the VHI system must provide high diffraction efficiency in a single diffraction order with high angular and wavelength selectivity. These characteristics can Fig.…”
Section: Handle Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relay was configured for 1:1 imaging to image the pupil of the microscope objective at the hologram plane, which allows the hologram to be the limiting aperture of the system and reduces beam overfill issues. 18 The holograms used in the VHI system must provide high diffraction efficiency in a single diffraction order with high angular and wavelength selectivity. These characteristics can Fig.…”
Section: Handle Opticsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] The number of simultaneous depth views is determined by the number of gratings being multiplexed into the holographic element, and reports of 2 to 5 depths have been reported using the multiplexing techniques. 24 As an optical system that is capable of concurrent visualization of surface and subsurface tissue structures, the development of endoscopic VHI systems can assist in reducing the number of unnecessary surgical procedures, such as prophylactic oophorectomies.…”
Section: Introductionmentioning
confidence: 99%
“…However, if light with a specific wavelength is not spatially separated along the x axis in object space, the optical sectioning performance degrades due to multiple combinations of wavelength and angle that are Bragg matched within the volume object. It has been shown that for broadband illumination of an object, the out-of-focus object points are not completely rejected by the volume hologram [7][8][9][10][11][12]. There are many combinations of wavelengths and angles within the spectral bandwidth of the source and the FOV that match the Bragg condition of the hologram and are therefore diffracted.…”
Section: Principles Of Operation and Backgroundmentioning
confidence: 99%
“…As an alternative, volume holographic imaging (VHI) has been shown to provide images from multiple depths within biological tissue samples without the need for scanning [1,2]. The VHI system (VHIS) can image multiple depths simultaneously with bright-field illumination using a light-emitting diode (LED) source [3][4][5][6][7][8][9][10]. In these systems, however, it has also been shown that the VHIS produces less-than-optimal depth resolution due to the wavelength-position degeneracy [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] The hologram is recorded by exposing a photosensitive polymer, 1,9-phenanthrenequinone-doped poly(methyl methacrylate) (PQ-PMMA), to an optical interference pattern formed with coherent laser illumination. To multiplex, a separate hologram is recorded into the same region of the element that will select light from a separate depth within the tissue sample.…”
Section: Introductionmentioning
confidence: 99%